Assistance in the preparation of academic study materials on traditional villages in West Papua Province: conservation and development of customary peoples - Warami, Hugo (Universitas Ahmad Dahlan, Yogyakarta, 2021)
Practical problems from the presidential and development of customary peoples form traditional villages legally based on applicable laws and regulations. This mentoring program aims to increase the knowledge, attitudes, and skills of the provincial and district/city apparatus in understanding village and customary village administrations. The target is to discuss how the assets and potential of villages in West Papua Province can be identified as ingredients in preparing academic studies on traditional villages. The output is expected to contribute to (1) understanding the territory and characteristics of culture in West Papua and (2) Develop recommendations for forming institutions that can support custom and cultural preservation in West Papua. This activity uses a Participatory Exercise Model or Participatory Andragogi for adults with lecture, training, and assistance methods. Mentoring activities took place from 07-07 December 2019. The activity classification consists of elements (1) of the provincial Government and regency/cities throughout West Papua, (2) universities, (3) customary institutions, (4) women activists, and (5) Head of the Big Man (Big Man) with 75 participants and eight speakers. The impact of this activity is the congestion of provincial regions on traditional villages, and technical institutions related to the coaching and empowerment of villages can carry out the process of establishing traditional villages.